KEANEKARAGAMAN DAN STATUS PERLINDUNGAN SATWALIAR DI PT. RIAU SAWITINDO ABADI - Harnios Arief; Joko Mijiarto; Ainur Rahman (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Forest land clearing withoutt appropriate method for oil palm plantations can reduce the diversity of wildlife in that area. To decrease these impacts, data of wildlife diversity and the distribution needs to be known, so that it can be determined which area can be opened or must be maintained. The research was to determine the diversity and conservation status in PT. Riau Sawitindo Abadi (PT. RSA). The Research was conducted in April 2015. Data was collected by interview, literatur studies and field observation (direct and indirect observation). The results showed that the RSA is a habitat for 78 wildlife species which consists of 52 species of birds (13 species protected), 16 species of mammals (13 species protected) and 10 species of reptiles (5 species protected). Forest area of PT. RSA has an important role as the habitat as well as a corridor for these animals. Keywords: biodiversity, conservation status, habitat, land clearing, wildlife